Biochemical and Botanical Aspects of Allium sativum L. Sowing - Ali Ammarellou; Ali Reza Yousefi; Moslem Heydari; Daniela Uberti; Andrea Mastinu (BioTech, 2022)
The main aim of this study was to evaluate the yield and compliance of selected Iranian garlic (Allium sativum L.) cultivars, including Tuyserkan (TSN), Heydareh (HDH), Mouien (MUN), and Taroom (TRM), during two growing seasons. The TRM cultivar germination rate is higher than the other cultivars studied. The TRM cultivars have quite remarkable values for the dry weight, fresh weight, stem diameter, and the number of leaves present. The fresh weight and dry weight of the TRM cultivar for the second year are 33.8 t/ha and 16.7 t/ha, respectively. However, on average, the HDH cultivar is the tallest plant in the experiments. Average pyruvic acid content in fresh samples of the TRM and HDH cultivars is 78 µm/gfw and 69.3 µm/gfw, respectively. It is observed that there are remarkable differences in the level of pyruvic acid between the different cultivars. The growth, development, and yield of plants are highly dependent on their genetic characteristics; in this experiment, the TRM cultivar shows a good yield (16.7 t/ha), and the evaluated characteristics improve compared to the other cultivars studied, which could be due to the high compatibility of this cultivar to the environmental conditions of the study. The excellent performance on the yield of TRM makes this cultivar more appreciable on a commercial level.